A critical discourse analysis of the representations of sex trafficking victims in Malaysia / Puspalata C Suppiah - Puspalata , C Suppiah (2019)
Trafficking of women for sexual purposes has been a major cause of concern in recent years. It is a global phenomenon that has spread extensively in both developing and developed countries. In Malaysia, sex-trafficking victims have been subjected to severe marginalisation in society unlike other social groups such as migrants and refugees. Within the legislation, victims are criminalised and treated as illegal immigrants, and therefore charged with immigration offences. More critically, the conflation between the terms “victims of sex trafficking” and “prostitutes” has led to the use of the terms interchangeably by popular mainstream newspapers in Malaysia. The disparity that exists between both groups can negatively impact on victims’ lives, giving rise to a growing body of literature that criticises the discourse of trafficking. The way sex-trafficking victims are represented differently could further lead to the denial of sex trafficking as a legitimate concern in Malaysia. In order for sex trafficking to be viewed as an important and urgent human rights issue, it is necessary to highlight the ways in which victims are represented and explain why certain representations can be damaging for such a social group. In this study, the representation of sex-trafficking victims is explored from two perspectives: the media and interview narratives. The Discourse-historical Approach (DHA) and Sociosemantic Network of Social Actors were primarily used as frameworks to examine the media representation of sex-trafficking victims. A total of 120 newspaper articles between 2010 and 2016 were selected for analysis. Victims’ personal experiences and self-representations were also examined through a Thematic Narrative Approach based on interview data of 15 women from five Southeast Asian countries. The interviews were conducted both at a national shelter home for rescued sex workers and in the field. Analysis of media texts revealed foreign women in sex work being commonly depicted as offenders in terms of legislation, rather than as victims of sex trafficking. Victims’ voices remain underrepresented while an extensive amount of space was given to prominent and elite social actors. Analysis of the interview narratives led to the emergence of four main themes that drew attention to victims’ vulnerability and lack of power. In particular, the stigma of “whore” attached to sex work had affected the women despite their legitimate victim status. Analysing the voices of women in sex work offers new perspectives about sex-trafficking issues that are affecting millions of women in society and ensures that research is responsive to their needs since it is through these women’s voices that “unheard” stories are exposed. Additionally, the knowledge generated from this study could provide insights for newspaper journalists so that they become more sensitive and responsible of the media coverage on sex trafficking as well as promote legislative reform about sex trafficking.